Low‐carbon power system operation with disperse carbon capture‐transportation‐utilization chain - Song, Zhenzi; Wang, Xiuli; Zhao, Tianyang; Hesamzadeh, Mohammad Reza; Qian, Tao; Huang, Jing; Li, Xin (IET generation, transmission & distribution, 2024)
The carbon capture‐transportation‐utilization (C‐CTU) chain strengthens the coupling between terminal energy consumption and renewable energy resources (RES), achieving carbon emission reduction in power generation sectors. However, the dynamic operation of the C‐CTU chain and the uncertainties induced by RES output pose new challenges for the low‐carbon operation. To address above challenges, the nonlinear dynamic operation model of C‐CTU chain is first proposed in this study. It is further incorporated into the day‐ahead operation scheme of the electricity‐carbon integrated system considering the stochastic nature of wind power. This scheme is treated as a two‐stage stochastic integer programming (TS‐SIP) problem with a mixed‐integer nonlinear recourse. By means of the polyhedral envelope‐based linearization method, this recourse is reformulated into its linear counterpart. To further improve the computational performance of classical decomposition algorithms, a novel Benders decomposition framework with hybrid cutting plane strategies is proposed to obtain better feasible solutions within a limited time. Simulations are conducted on two power system test cases with the C‐CTU chain. Numerical results indicate that the engagement of C‐CTU chain promotes the low‐carbon economic operation of the power system. Also, the proposed decomposition algorithm shows a superior solution capability to handle large‐scale TS‐SIP than state‐of‐the‐art commercial solvers. Nonlinear dynamic model of Carbon Capture‐Transportation‐Utilization Chain is established. A TS‐SIP model for the day‐ahead operation scheme of the electricity‐carbon integrated system is constructed. An efficient Benders decomposition framework is designed